Incidence and risk factors of adjacent segment disease following short segment posterior instrumentation in Bahraini patients: a five-year retrospective analysis - AlAnsari, Noor M.; Toorani, Badriya A.; Shujaie, Mohamed H.; Hussain, Rola M. (International Journal of Research in Orthopaedics, 2025)
Background: Despite advances in spinal surgery, adjacent segment disease (ASD) and adjacent disc degeneration (ADD) remain notable postoperative complications following spinal fusion, mainly due to suspected increased biomechanical stress that leads to adjacent disc degeneration. This research focuses on the Bahraini population, utilizing MRI to compare pre-op and post-op Adjacent disc conditions to identify the incidence and risk factors of ASD and ADD after short segment spinal fusion. Methods: A retrospective cohort study conducted over a five-year period at Salmaniya Medical Complex, the largest tertiary care center in the Kingdom of Bahrain. Reviewing pre-operative and post-operative MRI scans of 41 symptomatic patients who underwent short segment spinal fusion between 2014 and 2019. Patients were selected based on specific pre-operative and post-operative criteria developed by the orthopaedic team and were followed up to October 2023. Statistical analyses were performed using R software. Results: The analysis of 41 patients revealed a significant incidence of adjacent segment changes and the main risk factor that showed significance was advancing age. While other reported risk factors like level of fusion and number of fused segments did not significantly correlate with advancing ADD or ASD. There was no statistically significant association between hypertension, diabetes or multiple comorbidities and worsening conditions for either ASD or ADD post operation. Conclusions: The findings from our study contribute to the understanding of ASD and ADD after lumbar fusion surgeries, particularly in highlighting the significance of age. These insights can aid surgeons in better anticipating the risks associated with specific demographic and clinical profiles. More controlled studies on larger populations will help delineate more concrete risk factors.